Peningkatan Literasi Keuangan dan Penerapan Sistem Pencatatan Sederhana Bagi UMKM di Lingkungan Ikatan Keluarga Minang Samarinda - Emil Riza Putra; Muslimin B; Richa Rachmawati Afag; Fanny Ramadhani; Wike Pratiwi; Fajar Ramadhani; Syafei Karim; Risna Nona; Claudia Regina Kapuangan; Maysita Maysita (Departemen Budidaya Tanaman Perkebunan, Fakultas Pertanian, Universitas Andalas, 2026)
Micro, Small, and Medium Enterprises (MSMEs) within the Minang Family Association (IKM) in Samarinda are a key driver of the local economy. Initial observations indicate that the majority of these MSME actors face constraints in managing their business finances in a structured manner using information systems. The core problems identified are low financial literacy and the lack of a simple yet sustainable financial recording system. This is due to difficulties in separating personal and business finances, managing cash flow, and evaluating business progress. The objective of this community service initiative by the Accounting Information Systems Study Program of the State Agricultural Polytechnic of Samarinda is to enhance understanding and skills in basic financial literacy, as well as to introduce and guide business owners in implementing a simple IT-based financial recording system. The implementation methods include socialization and education on financial literacy, followed by training and mentoring in simple bookkeeping using software/application tools. The activity results demonstrated a significant improvement in the participants' understanding of financial management, asset separation, and IT-based financial planning. Consequently, the participants were able to create and implement simple financial records to track income, expenses, and receivables/payables. This community service program by the Accounting Information Systems Study Program has successfully empowered the MSMEs of the Minang Family Association in Samarinda, leading to transparent and accountable UMKM management. This empowerment is expected to enhance their competitiveness, access to capital, and support the professional growth of Minang specialty culinary businesses in Samarinda City.